Dinamika Hubungan Islam dan Lokalitas: Perebutan Makna Keislaman di Madura - Ahmad Zainul Hamdi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2018)
The discussion about Islam and local culture has resulted in a number of monumental academic works. The relation of Islam and the Javanese culture along with its dynamics have frequently colored intellectual debates in the field. Among the din of such fascinating academic debates, Islam Madura has been nearly neglected as an uninteresting academic discourse to observe. It has been argued that Madura is viewed as a “back door” of Java. It implies that observing Java means observing Madura automatically. This study seeks to raise the issue of contestation over the meaning of Islam within the relational context between Islam and the local culture of Madura society. Based on field research conducted under the light of Beatty’s multi-vocality concept, the study finds that Islam Madura is a communal identity, but it defines nothing about the Madurese Muslim community in general. Although each group acknowledges Islam as a shared identity, every individual and group, or sub-group, will have no a common understanding about the meaning of Islam. Islam has, certainly, unified all the Madurese people within a common perspective of mankind, God, and worldly matters, but this identity represents no one and does not specifically define any conception of anyone. The meaning of Islam Madura has been, therefore, endlessly knitted within compromising and synthesis process.